Sotos syndrome (cerebral gigantism): analysis of 8 cases - Débora Gusmão Melo; Angelina Xavier Acosta; Maria Aparecida de Almeida Salles; João Monteiro de Pina-Neto; José Daniel Vieira de Castro; Antonio Carlos Santos (Arquivos de Neuro-Psiquiatria)
Sotos syndrome or cerebral gigantism is characterized by macrocephaly, overgrowth, mental retardation and central nervous system abnormalities. Congenital heart defects may be present. We report 8 patients with this syndrome and relate their clinical features, neuroimaging and echocardiographic findings.